2014
DOI: 10.1189/jlb.0113053
|View full text |Cite
|
Sign up to set email alerts
|

Replenishment of the B cell compartment after doxorubicin-induced hematopoietic toxicity is facilitated by STAT1

Abstract: STAT1 serves as an important regulator in the response to pathogens, oncogenic transformation, and genotoxic insults. It exerts these effects by shaping the innate and adaptive immune response and by participating in genotoxic stress pathways, leading to apoptosis and inhibition of cell proliferation. We have investigated the role of STAT1 in hematopoietic toxicity induced by doxorubicin in STAT1-proficient and -deficient mice. Whereas the early genotoxic effect of doxorubicin did not depend on STAT1, expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…18,28,29 The administration of Dox has been shown to cause toxicity and the depletion of leukocytes. 31,32 The results of the present study showed that free Dox induces both quantitative and qualitative changes in the leukocytes. The group of mice treated with free Dox exhibited a substantial reduction in leukocyte count compared to the groups injected with Lip-Dox or a combination of Lip-Dox and glycosphingosomes.…”
Section: Discussionmentioning
confidence: 73%
“…18,28,29 The administration of Dox has been shown to cause toxicity and the depletion of leukocytes. 31,32 The results of the present study showed that free Dox induces both quantitative and qualitative changes in the leukocytes. The group of mice treated with free Dox exhibited a substantial reduction in leukocyte count compared to the groups injected with Lip-Dox or a combination of Lip-Dox and glycosphingosomes.…”
Section: Discussionmentioning
confidence: 73%
“…1). The team of Wolfgang Doppler and colleagues [2] focused on basic and preclinical cancer research questions and consequences for the hematopoietic system upon anthracycline treatment. This work will be placed in context below, but we highlight first the JAK-STAT pathway in association with cancer research.…”
mentioning
confidence: 99%
“…No obvious defects in B lymphopoiesis were described to date. It was so far poorly characterized that STAT1 is also required for normal hematopoietic cell development and maintenance of homeostasis, and a role especially upon hematopoietic challenge, e.g., after chemotherapy, has now been reported by Datta et al [2]. A role for STAT1 upon response to various chemotherapeutic drugs was recognized early in human cancer cell line studies, but in vivo animal studies with genetic loss of Stat1 proving this concept were lacking.…”
mentioning
confidence: 99%
See 2 more Smart Citations